Paraguay : Fifth Review Under the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Paraguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The rebound in inflation since mid-2007 is mostly owed to a jump in food prices in Paraguay. The price volatility of fruits and vegetables explains the divergence between headline and core inflation indicators observed in 2007. Following a decline that started in 2006, core inflation has risen in the second part of 2007. High export volume growth, coupled with a slowdown in import growth, have led to a turn around in the current account from a small deficit in 2006 to a surplus of about 1 1\2 percent of GDP in 2007.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet